ANALISIS PRAKTIK MAHKAMAH KONSTITUSI DALAM MENENTUKAN PERTENTANGAN NORMA HUKUM DALAM PUTUSAN PENGUJI~ UNDANG-UNDANG TERHADAP UNDANG-UNDANG DASAR 1945 - , TANTO LAILAM, SH, Moh. Fajrul Falaakh, S.H., M.A., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Th e ABSTRACT research studies is about the practice analysis of constitutional court to determine the conflicting legal norms, include of problems: juridical argument, the review based on Pancasila and Articles of 1945 Constitution, criteria of conflicting legal norms and criteria of non constitution as review standard. The normative legal research is used of statute approach, analytical approach, case approach. The result of this study has showed that Pancasila, Articles of 1945 Constitution, non constitution as the standard to constitutional review in Constitutional Court of Indonesia, with diverse argument. Formal examination (formale toetsingrecht) (Constitutional Court Decision No.27/PUU-VII/2009), argument: the conflicting legal norms againts the general principles of law making process (algemene beginselen van behoorlijke wetgeving), for example: fairness principle). Material examination (materiale toetsingrecht) (Constitutional Court Decision No.48/PUU-IX/2011, No.49/PUU-IX/2011 dan No.5/PUU-IX/2011), argument: is used interpretation method, for example: original and non original interpretation about public interest). Sociological examination (Constitutional Court Decision No.018/PUU-I/2003 dan No.8/PUU- VII/2010, juridical argument covering: differences of based on contitution, sociological argument, and so on. in determin Formal examination have a criteria ed of the conflicting legal norms, if facts of law making process can be assessed with value of Fourth Article of Pancasila and legal substance of Article 5 paragraph (1), Article 20, Article 21, Article 22A of 1945 Constitution and conflicting legal norms againt the general principles of law making process. Material examination, if conflicting legal norms can be assessed with 1945 Constitution, be through interpretation of the Constitutional Court judge. Sociological examination of criteria is: differences of based on contitution, conflicts between laws againt 1945 Constitution. The Non Constitution as condition, include: First, non-constitutional norm is a norm of the delegation of the 1945 Constitution, Second, nonconstitutional substance is a substance or material that must be regulated in the Laws. Third, as the norm implementation at a law making process.